Student selection to a rural veterinary school. 1: applicant demographics and predictors of success within the application process. Issue 6 (28th May 2019) - Raidal, SL; Lord, J; Hayes, LM; Hyams, J; Lievaart, J
Abstract : Objective: To determine demographic details of applicants to the veterinary degree program at and relate this information to student selection processes. Design: Retrospective evaluation of applicant data. Methods: Database records of 4042 applicants to the veterinary program (2006–2016) were retrieved from university records. Summary statistics were used to determine basic demographic data, which were related to pre‐entry academic achievement and results of selection processes using univariable and multivariable analyses. Results: The number of applications, interviews and acceptance of offers fluctuated but did not vary substantively for the duration of the study. Gender, rurality (as assessed by residential and school postcodes), socioeconomic background, academic background and pre‐entry academic achievement all significantly influenced written application and interview scores in the multivariate models. Rural background, written application score, number of applications, pre‐entry academic history and achievement significantly affected the chances of receiving an interview. Chances of receiving an offer and subsequent program entry were significantly influenced by academic background, interview score and pre‐entry academic achievement. Male applicants were more likely to receive an offer, but gender had no effect on program entry. Rural residential and school background was associated with significantly reduced ATAR in comparison with city‐based applicants. Conclusion: Selection processes effectively identified applicants with demographic backgrounds and life experiences consistent with the School's commitment to the veterinary needs of rural and regional Australia. Findings support the provision of an academic loading for the ATAR results of rural students. Effects of these selection outcomes on student performance should be evaluated.